Topics in igneous petrology - Ray, Jyotisankar; Sen, Gautam; Ghosh, Biswajit (Springer Netherlands, 2011)
The second half of the past century witnessed a remarkable paradigm shift in approach to the understanding of igneous rocks. Global literature records a change from a classical petrographic approach to emphasis on mineral chemistry, trace element characteristics, tectonic setting, phase relations, and theoretical simulation of magma generation and evolution processes. This book contains contributions by international experts in different fields of igneous petrology and presents an overview of recent developments. This book is dedicated to the late Dr Mihir K. Bose, former professor of the Department of Geology, Presidency College, Calcutta, India, who actively participated in the development of this new global view of igneous petrology.